The effect of dates and honey extracts (phoenix dactylifera and apis mellifera) for increasing pregnant women’s haemoglobin - Erika; Yulia Irvani Dewi; Arneliwati (Journal of the Pakistan Medical Association, 2024)
Objective: To examine the effect of date fruit extract and honey in increasing haemoglobin levels in pregnant women. Method: The quasi-experimental study was conducted from July to August 2022 in Rumbai Pesisir Subdistric, Pekanbaru, Indonesia, and comprised anaemic pregnant women with haemoglobin levels <11gm/dl who were not consuming iron tablets or blood boosters. They were given honey and date extracts 2 tablespoons twice daily for two weeks. Haemoglobin level was checked at baseline and then at the end of each week of intervention. Data was analysed using SPSS version 20 and quantitative method by using bivariate analysis. Results: Of the 50 women, 59(98%) were aged 20-35 years, and 1(2%) was aged >35 years. Besides, 21(42%) women were in the second trimester, 17(34%) in third, and 12(24%) in the first trimester of pregnancy. The increase in haemoglobin levels post-intervention was highly significant (p=0.0001). Conclusion: Date fruit extract and honey increased haemoglobin level of pregnant women. Keywords: Phoenicia, Pregnancy Trimester, Iron, Haemoglobins, Honey, Hematologic, Anaemia.